2011
DOI: 10.1002/art.30513
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term and long‐term outcomes of interstitial lung disease in polymyositis and dermatomyositis: A series of 107 patients

Abstract: Objective. This study was undertaken to assess the characteristics and outcome of interstitial lung disease (ILD) in polymyositis/dermatomyositis (PM/ DM) and to determine variables predictive of ILD deterioration in PM/DM.Methods. Among 348 consecutive patients with PM/DM, 107 patients with ILD were identified by medical records search in 4 medical centers. All patients underwent pulmonary function tests (PFTs) and pulmonary high-resolution computed tomography (HRCT) scan.Results. ILD onset preceded PM/DM cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
212
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 42 publications
7
212
2
11
Order By: Relevance
“…5 In antisynthetase syndrome, myositis may present as either dermatomyositis (DM) or polymyositis (PM) [8][9][10] ; however, this association seems to be arbitrary, and is not clinically helpful.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…5 In antisynthetase syndrome, myositis may present as either dermatomyositis (DM) or polymyositis (PM) [8][9][10] ; however, this association seems to be arbitrary, and is not clinically helpful.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…6,7 Although it is unclear why AARS are recognized as autoantigens, theories that link ASA to autoimmunity have been proposed. 5 In antisynthetase syndrome, myositis may present as either dermatomyositis (DM) or polymyositis (PM) [8][9][10] ; however, this association seems to be arbitrary, and is not clinically helpful.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Moreover, certain causes require specific treatments. These treatments could be essential, as the long-term prognosis and the survival of patients with ASS, based on retrospective studies, showed a clear correlation with lung involvement [2,[18][19][20]. However, to date, the influence of cofactors associated with ILD, such as PH, has rarely been evaluated in large series.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse clinical outcome, with relatively high morbidity and mortality rates compared with those of other forms of inflammatory myosites, is primarily due to irreversible Some of the most common clinical entities and the corresponding HRCT patterns and histological features observed in patients with ASS are: 1) Cryptogenic Organizing Pneumonia (COP), characterized by patchy consolidations and/or nodules [56][57][58][59][60][61] ; the majority of histopatological changes center on small airways. There is a mild associated interstitial inflammatory infiltrate, type II cell metaplasia, and an increase in alveolar macrophages, some of which may be foamy.…”
Section: Discussionmentioning
confidence: 99%